ANALISIS EFEKTIVITAS PROSES PENGADAAN BARANGMELALUI SISTEM SMAR DI PLN UID S2JB - Khoiriah Maula Nanda; Aminullah Imal Alfresi (Jurnal Riset Sistem Informasi, 2025)
This study was conducted in the Planning Division of PLN UID S2JB with a focus on implementing the Supply Chain Management Marketplace (SMAR) as a digital procurement system aimed at improving the effectiveness and efficiency of material procurement, which is crucial for ensuring reliable electricity supply operations. Although SMAR was designed to accelerate processes, facilitate coordination, and enhance administrative transparency, its implementation still faces several challenges, including lengthy approval chains requiring multiple verification levels up to the central office, discrepancies in item quantities due to vendor stock limitations, and the suboptimal utilization of the Integrated Procurement Management System (IPMS), which results in some administrative documents still being processed manually. The objective of this research is to assess the effectiveness of SMAR using four key indicators—process speed, accuracy of goods received, ease of coordination, and transparency of documentation—while also providing recommendations for system improvements. This qualitative descriptive study employed observation, interviews with Planning Division staff, and documentation review of SMAR’s business processes. The findings indicate that SMAR has contributed positively, particularly in enhancing transparency and coordination, as procurement documents can be easily tracked and communication between units and vendors has improved; however, challenges remain in terms of process speed and quantity accuracy. Based on these findings, recommended strategies include implementing risk-based approval to streamline approvals without compromising control, integrating real-time vendor stock data to minimize quantity discrepancies, and optimizing IPMS to fully support document digitalization. These measures are expected to comprehensively improve SMAR’s effectiveness and contribute to PLN UID S2JB’s overall operational performance in the long term.